Stabilization and Control of Single-Wheeled Vehicle with BLDC Motor - Patrik Beno; Miroslav Gutten; Milan Simko; Jozef Sedo (Communications - Scientific letters of the University of Zilina, 2019)
To stabilize a single-wheel vehicle is necessary to know the angle of gradient of the platform with respect to the horizontal axis and also the movement of the vehicle. This can be detected in several ways. Accelerometers and gyroscopes are small, accurate and energy-saving today. They provide analogue or digital output. In the introduction we will describe the basic parameters of accelerometer and gyroscope. We will describe the principle of digital signal processing from both sensors. In the next section we look at the effect of dynamic acceleration on the sensors and the elimination of this phenomenon with a complementary filter. We explain, what it is a complementary filter, benefits and internal structure. We will include a short code in the C language for data processing from the output.